1976
DOI: 10.1083/jcb.70.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Growth control of differentiated fetal rat hepatocytes in primary monolayer culture. IX. Specific inhibition of DNA synthesis initiation by very low density lipoprotein and possible significance to the problem of liver regeneration.

Abstract: Rat serum very low density lipoprotein (VLDL) inhibits initiation of DNA synthesis in fetal rat hepatocyte cultures; cells engaged in synthesizing DNA resist inhibition. VLDL action is specific and apparently blocks prereplicative protein synthesis. These and other results, from studies of altered blood VLDL levels and [3H]thymidine incorporation into isolated liver nuclei in 70% hepatectomized normal and mutant hyperlipoproteinemic rats, as well as from infusion studies with a "mitogenic" hormone solution, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Although there are a number of studies describing lipoprotein inhibition of DNA synthesis for various cell types including a 3T3 fibroblast line (Ito et al, 1982;Leffert and Weinstein, 1976;Takii et al, 1983), in our system LDL does not diminish DNA synthesis unless it is oxidized. The inhibition by o-LDL of 3H-thymidine incorporation into DNA appeared to be distinct from o-LDL-induced cytotoxicity in that more severely oxidized LDL both blunted 3H-thymidine incorporation and caused cell death (Figs.…”
Section: Discussionmentioning
confidence: 88%
“…Although there are a number of studies describing lipoprotein inhibition of DNA synthesis for various cell types including a 3T3 fibroblast line (Ito et al, 1982;Leffert and Weinstein, 1976;Takii et al, 1983), in our system LDL does not diminish DNA synthesis unless it is oxidized. The inhibition by o-LDL of 3H-thymidine incorporation into DNA appeared to be distinct from o-LDL-induced cytotoxicity in that more severely oxidized LDL both blunted 3H-thymidine incorporation and caused cell death (Figs.…”
Section: Discussionmentioning
confidence: 88%
“…These included the direct regeneration indexes of DNA synthesis, labeled nuclei and subsequent mitosis (3)(4)(5). Surrogate manifestations of regeneration also were monitored: systemic insulin and glucagon; circulating sex steroid hormones and their nuclear and cytosolic liver receptors (6)(7)(8)(9)(10)(11)(12); and the expression of transforming growth factor-p (TGF-P) mRNA (13, 141, c-Ha-rus mRNA (15) and c-jun mRNA (16,17). These changes after transplantation of small-for-size livers were compared with those occurring after transplantation of size-matched livers.…”
mentioning
confidence: 99%
“…This lipid is probably bound to a carrier with much higher mole cular weight, since it was not dialyzed from the heated MCG3AF (table IV). Some authors have found that VLDL have immunosuppressive properties [15] and others that VLDL inhibit DNA synthesis [14], After removing VLDL from MCG3AF, however, its activ ity still remained (table V). This suggests that this activity cannot be attributed to these lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…As Leffer and Weinstein [14] have reported, VLDL inhibit the initiation of DNA replication in embryonic hepatocytes. We removed these lipoproteins from the 70°C heated and dialyzed MCG3AF by partial delipidation, finding that this treatment did not ap preciably reduce the inhibitory activity of MCG3AF (table V).…”
Section: Additional Treatment Of Mcg3afmentioning
confidence: 99%